A novel method to measure sensory nerve conduction of the supraclavicular nerve. Issue 6 (30th October 2014) - Hemmi, Shoji; Kurokawa, Katsumi; Nagai, Taiji; Murakami, Tatsufumi; Sunada, Yoshihide
ABSTRACT Introduction: In this report we describe a reliable method for recording sensory nerve action potentials (SNAPs) of the supraclavicular nerve. Methods: Supraclavicular SNAPs were recorded by placing a surface active electrode at the posterior border of the sternocleidomastoid muscle at a distance of 6 cm from the sternoclavicular joint. The nerve was stimulated at the lower border of the clavicle 4.5 cm lateral to the sternoclavicular joint. Results: Supraclavicular SNAPs were recorded bilaterally from 20 healthy volunteers. Mean onset latency was 1.0 ± 0.2 ms, and mean peak latency was 1.4 ± 0.3 ms. Mean baseline‐to‐peak amplitude for the SNAPs was 6.1 ± 2.2 µV, and mean maximum conduction velocity was 59.8 ± 6.2 m/s. The mean percentage of side‐to‐side difference in amplitude was 12.9 ± 11.0%. Conclusions: Supraclavicular SNAPs could be obtained in all normal subjects. Assessment of supraclavicular nerve conduction is very useful in the diagnosis of supraclavicular neuropathy Muscle Nerve 50: 1005–1007, 2014